Abrasive machining with MQSL. - Morris, Tom (Cranfield University, 2011)
Grinding and polishing of engineered components are critical aspects of the precision manufacturing of high performance, quality assured products. Elevated process temperatures, however, are a common and for the most part undesirable feature of the grinding process. High process temperatures increase the likelihood of microstructural change within the immediate subsurface layer and are detrimental to the strength and performance of the manufactured products. Increasing processing costs and tighter environmental legislation are encouraging industry to seek innovative fluid application techniques as significant savings in production can be achieved. In this context, and with sponsorship from three industrial partners, namely; Fives Cinetic, Fuchs Lubricants plc and Southside Thermal Sciences Ltd, and also from the Engineering and Physical Science Research Council (EPSRC), this research aimed to develop an understanding of Minimum Quantity Solid Lubrication (MQSL) as a method for abrasive machining, with particular reference to the control of surface temperatures. Improving the lubricity of Minimum Quantity Lubrication (MQL) fluids reduces the frictional source of process heat and controls the finish surface temperature. The application of effective solid lubricants is known as Minimum Quantity Solid Lubrication (MQSL). Molybdenum Disulphide (MoS2), Calcium Fluoride (CaF2), and hexagonal Boron Nitride (hBN) were compared against a semi-synthetic water soluble machining fluid (Fuchs EcoCool). A series of Taguchi factorial experimental trials assessed their performances through ANOVA (ANalysis Of VAriance) statistical method. The hBN produced the lowest grinding temperatures of the solid lubricants tested, although they still remained higher than those achieved using the EcoCool control. The reduction of the machining fluid enabled a Charged Coupled Device (CCD) sensor to be fitted into the grinding machine. The recorded movement in the emitted spectrum from the grinding chips was compared to experimental and modelled process temperatures. This showed that the wavelengths of the chip light correlated to the temperature of the finish grinding surface. This greatly contributed to determining the feasibility of constructing a non-destructive, non-invasive, thermally-adaptive control system for controlling grinding surface temperatures.